-(y-5)+8=6

Simple and best practice solution for -(y-5)+8=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(y-5)+8=6 equation:



-(y-5)+8=6
We move all terms to the left:
-(y-5)+8-(6)=0
We add all the numbers together, and all the variables
-(y-5)+2=0
We get rid of parentheses
-y+5+2=0
We add all the numbers together, and all the variables
-1y+7=0
We move all terms containing y to the left, all other terms to the right
-y=-7
y=-7/-1
y=+7

See similar equations:

| 1.75=8.75/y | | (6x-6)=720 | | 2(z+1)-1=9 | | 4x-13+13=23+13 | | x—7.6=4.3 | | k+37=972 | | 92=-5y-13 | | Y=3.25(x-×25) | | q=407=566 | | 44-8x=44-5x | | 7d-2=54 | | r-960=24 | | 455=40x+12(1.5x) | | 115=6v+7 | | 25=x/2+4 | | 3+2x+7=12 | | 11=s/24 | | 4(x-2)-5=23 | | 57=16+x | | f/31=18 | | 4(x−2)−5=2/3 | | -7–x=12 | | 1-4|x|=-11 | | 4(x−2)−5=23 | | 9=y/13 | | (3x-1)=58 | | 16g=672 | | (1/3)(6x-27)=1 | | 9^6x=27 | | 9^6x=7 | | 6=6-2d | | h-82=508 |

Equations solver categories